2017
DOI: 10.2106/jbjs.16.00628
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Osteosynthesis with a Bridge Plate Versus a Functional Brace for Humeral Shaft Fractures

Abstract: Therapeutic Level I. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
116
0
13

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(140 citation statements)
references
References 30 publications
11
116
0
13
Order By: Relevance
“…At the 1-year follow-up visit, all fractures were healed and none of the patients had suffered non-union, an outcome better than that reported for other treatment methods [ 1 , 2 , 5 , 9 , 21 23 ]. The mean union times of the Synbone group and the 3D-printed groups were 16.16 and 15.57 weeks, respectively, which was similar to other studies even though our patients were older than in other studies [ 11 , 17 , 24 ].…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…At the 1-year follow-up visit, all fractures were healed and none of the patients had suffered non-union, an outcome better than that reported for other treatment methods [ 1 , 2 , 5 , 9 , 21 23 ]. The mean union times of the Synbone group and the 3D-printed groups were 16.16 and 15.57 weeks, respectively, which was similar to other studies even though our patients were older than in other studies [ 11 , 17 , 24 ].…”
Section: Discussionmentioning
confidence: 64%
“…The optimal treatment for humeral shaft fracture remains controversial. Although a large proportion of these fractures can be treated without surgery, a recent study, involving a randomized controlled trial, compared bridge plate with functional brace fixation for humeral shaft fractures and concluded that surgical plating has a statistically significant advantage with a better DASH score, lower non-union rate, and lower residual deformity rate [ 1 ]. As for proximal third humeral shaft fractures, they were thought to be complicated with a higher non-union rate when treated conservatively compared with middle and distal fractures [ 2 , 5 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these angular deformities are generally well tolerated with minimal functional impairment [1, 2, 11 -13]. Matsunaga et al, compared surgical fixation and functional bracing and found patients who were fixed had higher DASH scores, higher rates of union, and less anteroposterior residual angulation [14]. However, there were no differences with regards to the SF-36 score, pain level, and Constant score.…”
Section: Discussionmentioning
confidence: 99%
“…Die Inzidenz von Pseudarthrosen beträgt im proximalen Schaftdrittel 24 %, im mittleren Drittel 12 % und im distalen Schaftdrittel 15 % [5]. Obgleich manche Studien bei frischen Schaftfrakturen eine ähnliche Ausheilungsrate und Ausheilungszeit für konservativ behandelte PatientInnen im Vergleich zu operativ versorgten PatientInnen angeben, gibt es doch eine gewisse Evidenz, dass die Osteosynthese (Plattenosteosynthese) zu einer deutlich geringeren Rate an Fehlverheilungen und Pseudarthrosen führt [6,7]. Auch im eigenen Krankengut können die hohen Ausheilungsraten, die von Sarmiento et al [1] angegeben wurden, mit der Brace-Behandlung nicht erreicht werden.…”
Section: Humerusschaftunclassified